When collagen fails: Zinc isotopes unlock Sumerian lifeways in southern Mesopotamia - Matteo Giaccari; Licia Romano; Silvia Soncin; Sofia Panella; Francesca Alhaique; Franco D’Agostino; Klervia Jaouen; Mary Anne Tafuri (Proceedings of the National Academy of Sciences, 2026)
Reconstructing past lifeways and diets is essential to understanding the emergence of urban societies. However, in what are now arid environments like southern Mesopotamia, poor collagen preservation has long hampered direct isotopic analysis of trophic levels. This limitation has left key gaps in our understanding of subsistence in one of the world’s earliest urban heartlands. Here, we apply zinc isotope analysis to human and faunal dental enamel from the third-millennium BCE site of Abu Tbeirah (Iraq), integrating δ 13 C, δ 18 O, and trace element ratios (Ba/Ca and Sr/Ca). This multiproxy approach reveals an omnivorous diet based on C 3 cereals, terrestrial animal products (likely including pigs), and limited freshwater resources, with no or little evidence of marine fish consumption, despite the site’s proximity to the ancient shoreline. Dietary patterns do not vary by sex, suggesting broad access to similar food sources within this nonelite population. Moreover, zinc and carbon isotopes proved valuable in identifying animal feeding practices. Our results provide direct dietary evidence from southern Mesopotamia, overcoming long-standing preservation challenges. The results allow us to evaluate specific expectations about diet and animal management in a collagen-poor context, also highlighting early-life feeding behaviors. They demonstrate the power of zinc isotopes to reconstruct trophic level in collagen-poor contexts, opening broad avenues for bioarchaeological research in early complex societies.